1993
DOI: 10.1021/ac00056a010
|View full text |Cite
|
Sign up to set email alerts
|

Suppressed conductometric capillary electrophoresis separation systems

Abstract: A tubular cation-exchange membrane Is Installed at the end of a 60-cm-long 75-gm-bore fused-slllca capillary. A static dilute acid regenerant solution surrounds the membrane that functions as a suppressor. With positive high voltage applied to the capillary Inlet and the regenerant solution grounded, effective suppression of electrolytes such as solutions of alkali metal borate, glyclnate, or cyanide Is observed. Electroosmotlc flow carries the capillary effluent past the suppressor Into a conductivity detecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(42 citation statements)
references
References 23 publications
0
42
0
Order By: Relevance
“…In ion chromatography, very low detection limit at ppb (ng/mL) level can be reached by background depression. Introduction of background depression normally used in ion chromatography was also found effective in CE as demonstrated in the reports [27,28].…”
Section: Capillary Chip Electrophoresis With Conductivity Detectionmentioning
confidence: 97%
“…In ion chromatography, very low detection limit at ppb (ng/mL) level can be reached by background depression. Introduction of background depression normally used in ion chromatography was also found effective in CE as demonstrated in the reports [27,28].…”
Section: Capillary Chip Electrophoresis With Conductivity Detectionmentioning
confidence: 97%
“…In 1993, two different research groups reported the use of a suppressor in combination with contact conductivity detection in CE [20,22]. Dasgupta and Bao [22] coupled a Nafion membrane between two pieces of fused-silica capillary.…”
Section: Contact Conductivity Detection In Capillariesmentioning
confidence: 99%
“…Similarly to ion-chromatography single-column and the suppressed one, introduction of suppressed conductivity detection to CE allows fot the decrease of the limit of detection for common organic and inorganic ions to the level 1 ± 10 ppb [180,181]. As is shown in Figure 9, the suppressor is made from a short ion-exchange membrane capillary and placed between the separation capillary and the ion-chromatography conductivity detector, with one of the conductivity electrodes being grounded.…”
Section: Conductivity Detection In Cementioning
confidence: 99%